Incidence of acute otitis media in children below 6 years of age seen in medical practices in five East European countries. Issue 1 (December 2016) - Usonis, Vytautas; Jackowska, Teresa; Petraitiene, Sigita; Sapala, Alicja; Neculau, Andrea; Stryjewska, Izabella; Devadiga, Raghavendra; Tafalla, Monica; Holl, Katsiaryna
Abstract Background Although acute otitis media (AOM) remains a major public health problem worldwide and brings economic burden on health care system and caregivers, little information is available about its epidemiology in Eastern Europe. Methods We conducted an epidemiological, prospective, observational, multi-centre cohort study (NCT01365390) in five East European countries (Estonia, Lithuania, Poland, Romania and Slovenia) between June 2011 and January 2013 to determine the incidence and clinical characteristics of AOM among children aged < 6 years during 1 year. Results AOM incidence was 160.7 cases (95 % confidence interval [CI]: 144.7–177.9) per 1000 person-years (PY) being the lowest in the < 1 year age group (92.3 cases [95 % CI: 59.7–136.2] per 1000 PY) and the highest in the 3– < 4 years age group (208.9 cases [95 % CI: 165.1–260.7] per 1000 PY). AOM incidence was similar across the countries, with the exception of Slovenia (340.3 cases [95 % CI: 278.3–412.0] per 1000 PY). There was a lower risk in breastfed children and a higher risk in those attending school/childcare or with allergies. AOM required 521 visits to the doctor. Antibiotics were prescribed for 276 (74.8 %) episodes with the lowest prescription rate in Estonia (51.4 %) and the highest in Romania (83.7 %). Complications were rare and hospitalisations occurred in 2 % of the cases. Conclusions The disease burden of AOM in Eastern Europe is relevant and public health initiatives to reduce it should be considered. Trial registration ClinicalTrial.govNCT01365390 .